The effect of wind on electricity CO₂ emissions: The case of Ireland - Valeria Di Cosmo; Laura Malaguzzi Valeri (The Economic and Social Research Institute (ESRI), 2014)
This paper evaluates the effect of wind generation on CO2 emissions using 2008-2012 historical data for the Irish Single Electricity Market. Wind generation decreases CO2 emissions, but by less than the average system emissions. When we evaluate the results by technology, we find that wind generation has the same cumulative effect on emissions from both CCGT and coal plants, but displaces more generation from CCGTs than from coal for every MWh of wind. This result is driven by the high number of CCGT plants on the system, their flexibility and position in the merit order. Moreover, as wind displaces CCGTs, it also pushes them to generate less efficiently, displacing somewhat fewer CO2 emissions. Finally wind displaces about 5% fewer emissions when the pumped storage plants are on outage, suggesting that wind is more effective in more flexible systems.
Keywords: 330; Windenergie; Treibhausgas-Emissionen; Irland